Expectations and Strategies of Enterprises in the Period of Joining the European Union - Balaton, Károly (Theory, Methodology, Practice – Review of Business and Management, 2007)
The paper is based on a questionnaire survey conducted by the Competitiveness Research Centre at the Corvinus University of Budapest in 2004. The author analyses expectations of company managers concerning the possible consequences of joining the European Union. Managers perceived increasing level of uncertainty parallel with getting closer to the time of EU enlargement. They expected more severe competition expecially by companies of the EU 15 countries. The overall expectation on consequences for the company’s performance is positive. The last section of the paper provides an overview on the strategic preparation of companies for the competition within the European Union.